2015
DOI: 10.1016/j.actamat.2015.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Brittle versus ductile behaviour of nanotwinned copper: A molecular dynamics study

Abstract: Nanotwinned copper (Cu) exhibits an unusual combination of ultra-high yield strength and high ductility. A brittle-to-ductile transition was previously experimentally observed in nanotwinned Cu despite Cu being an intrinsically ductile metal. However, the atomic mechanisms responsible for brittle fracture and ductile fracture in nanotwinned Cu are still not clear. In this study, molecular dynamics (MD) simulations at different temperatures have been performed to investigate the fracture behaviour of a nanotwin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…[68][69][70][71][72][73][74] According to the molecular dynamics (MD) simulation results, the brittle/ductile deformation modes of NT metals can be affected by the thickness of materials and environmental temperature. 75,76 The plastic anisotropy has also been validated. [77][78][79][80] The exceptional torsion capability of nanowires is accessible by domino detwinning.…”
Section: Introductionmentioning
confidence: 99%
“…[68][69][70][71][72][73][74] According to the molecular dynamics (MD) simulation results, the brittle/ductile deformation modes of NT metals can be affected by the thickness of materials and environmental temperature. 75,76 The plastic anisotropy has also been validated. [77][78][79][80] The exceptional torsion capability of nanowires is accessible by domino detwinning.…”
Section: Introductionmentioning
confidence: 99%
“…This could delay the emission of dislocation in the substrate compared to the free surface. Although mechanical properties differences exist between the coatings and substrate, experiments and molecular dynamic simulations have demonstrated that the coatings could affect the plastic deformation of the substrate [24]. This is attributed to the different lattice parameters and crystalline structures of the brittle coatings from that of the metal substrate.…”
Section: Fatigue Behavior and Discussionmentioning
confidence: 99%
“…[1] shows that the defect emission and propagation in fivefold twinned silver nanowire is prevented by the preexisting twin boundaries. Creep mechanisms in nanotwinned metals [2], dynamics of grain boundary atoms in the bulk nanocrystalline aluminum [3], plastic deformation of nanocrystalline copper [4], deformation behavior of nanopillars with and without twin boundary [5], the fracture behavior of a nanotwinned Cu specimen [6,7], secondary twinning contribution to the ductility of the magnesium nanowire [8] Uniaxial tensile loading is dissatisfactory for complex stress states. The mechanics properties of gold twin nanocubes under different triaxial tensile rates are derived in this paper.…”
Section: Introductionmentioning
confidence: 99%